2016
DOI: 10.1515/aep-2016-0031
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of particle size and fractal dimensions of suspensions contained in raw sewage, treated sewage and activated sludge

Abstract: The analysis of particle size in suspensions carried out with use of the laser diffraction method enables us to obtain not only information about the size of particles, but also about their properties, shape and spatial structure, determined basing on fractal dimension. The fractal dimension permits the evaluation of the interior of aggregates, at the same time showing the degree of complexity of the matter. In literature, much attention is paid to the evaluation of the fractal dimension of fl ocs in activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…After reaching the stationary phase, flocs were retained on the pine bark filling, which resulted in a notable decrease of diameter of particles remaining in the volume of the treated sewage. This indicates that the size and shape of flocs has a significant effect on their properties and determines the method of their removal (Zhenhua et al 2001;Kuśnierz and Wiercik 2016;Huang et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After reaching the stationary phase, flocs were retained on the pine bark filling, which resulted in a notable decrease of diameter of particles remaining in the volume of the treated sewage. This indicates that the size and shape of flocs has a significant effect on their properties and determines the method of their removal (Zhenhua et al 2001;Kuśnierz and Wiercik 2016;Huang et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Together with other microorganisms, organic matter, and mineral matter, they form flocs which are characterised by multimodal size distribution and varied strength (Fettweis et al 2014). Determination of the size distribution of those particles in wastewater allows the choice of a suitable method of their removal (Bawiec et al 2017;Kuśnierz and Wiercik 2016;Huang et al 2010). That parameter, apart from density and porosity, is one of the factors in the estimation of the ability of flocs for sedimentation or flotation (Bawiec et al 2017;Wu and He 2012;Barbusiński and Kościelniak 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve fine regulation of the coagulation process, scholars have attempted to divide the coagulation process. Sweeping current detector (SCD) analysis [11], small-angle laser light scattering [12], and average floc size measurements have been used to identify the stage in which flocs start to grow, but the relevant parameters in these methods could not accurately reflect the changes in the flocs at later stages in the coagulation process. He et al [13] found that the fractal dimension of flocs provided a new way of studying the coagulation process, as the process of floc growth could be described with a fractal dimension model and divided into two distinct phases.…”
Section: Introductionmentioning
confidence: 99%
“…To optimize coagulants and coagulation conditions, Margaritis et al [19] and Amjad et al [20] compared the fractal dimension of flocs and the distribution of fractal dimension, and on this basis, they studied the coagulation mechanism in water treatment. Kuśnierz and Wiercik [11] further used particle size and fractal dimensions to measure the effects of coagulation in wastewater treatment.…”
Section: Introductionmentioning
confidence: 99%